Impact of Injection Duration and Injection Timing Variations on Torque and Power Output of the Ken Arok Urban Car Utilizing E100 Ethanol - Nike Nur Farida; Muhammad Rafi Akbar Yudhistira; Nicko Nur Rakhmaddian (Institute of Research and Community Outreach, Petra Christian University, 2024)
State Polytechnic of Malang (Polinema) actively participated in the energy-efficient car competition. The Polinema team has developed an energy-efficient car called Ken Arok, which competes in the urban ethanol class (Internal Combustion Engine) concept. This class emphasizes using internal combustion engines as the driving force and ethanol as the fuel. Ken Arok won fifth place in the competition due to obstacles in the programmed ECU program, especially in the injection duration. This study examines the effect of the interaction between injection duration and injection time variations on the torque and power output of the Ken Arok urban car fueled by E100 ethanol. An experimental approach was used in this study. A modified motor, converted into an energy-efficient urban car, was tested. The injection duration mapping was varied in multiples of 2 ms, with values ​​ranging from 2 ms less than the standard to 2 ms more than the standard. Likewise, the injection time was varied in multiples of 2 degrees, including 2 degrees less than the standard and 2 degrees more than the standard. The dyno tester measured the torque and power generated under these conditions. The main objective of this study was to identify the optimal torque and power settings for the Ken Arok energy-efficient engine. The highest torque value recorded was 10.13 N.m, achieved at 6000 rpm when using an injection duration of 2 ms more than the standard (9.06 ms) and an injection timing advanced by 2 degrees (3580). The peak power output reached 8.7 HP at 6000 rpm under compression injection duration plus 2 ms (9.06 ms), and when the injection was advanced by 20 (3580).